Preventability of early vs. late readmissions in an academic medical center. - Kelly L Graham; Ogechi Dike; Lauren Doctoroff; Marisa Jupiter; Anita Vanka; Roger B Davis; Edward R Marcantonio (PLoS ONE)
Background It is unclear if the 30-day unplanned hospital readmission rate is a plausible accountability metric. Objective Compare preventability of hospital readmissions, between an early period [0-7 days post-discharge] and a late period [8-30 days post-discharge]. Compare causes of readmission, and frequency of markers of clinical instability 24h prior to discharge between early and late readmissions. Design, setting, patients 120 patient readmissions in an academic medical center between 1/1/2009-12/31/2010. Measures Sum-score based on a standard algorithm that assesses preventability of each readmission based on blinded hospitalist review; average causation score for seven types of adverse events; rates of markers of clinical instability within 24h prior to discharge. Results Readmissions were significantly more preventable in the early compared to the late period [median preventability sum score 8.5 vs. 8.0, p = 0.03]. There were significantly more management errors as causative events for the readmission in the early compared to the late period [mean causation score [scale 1-6, 6 most causal] 2.0 vs. 1.5, p = 0.04], and these errors were significantly more preventable in the early compared to the late period [mean preventability score 1.9 vs 1.5, p = 0.03]. Patients readmitted in the early period were significantly more likely to have mental status changes documented 24h prior to hospital discharge than patients readmitted in the late period [12% vs. 0%, p = 0.01]. Conclusions Readmissions occurring in the early period were significantly more preventable. Early readmissions were associated with more management errors, and mental status changes 24h prior to discharge. Seven-day readmissions may be a better accountability measure.